2013
DOI: 10.1016/j.juro.2013.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Upper Tract Imaging Surveillance is not Effective in Diagnosing Upper Tract Recurrence in Patients Followed for Nonmuscle Invasive Bladder Cancer

Abstract: Upper tract recurrence is a lifelong risk in patients with bladder cancer, but most cases will be missed on routine upper tract imaging. The majority of upper tract urothelial carcinoma can be diagnosed using a combination of thorough history taking, physical examination, urine cytology and sonography, indicating that routine surveillance imaging may not be the most efficient way to detect upper tract recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 24 publications
1
23
1
1
Order By: Relevance
“…Sternberg et al [19] followed up 938 patients with NMIBC mainly with CT urography and demonstrated similar results. However, only 25% of patients with Ta tumors and 27% of T1 tumors who developed UTUC were diagnosed on routine imaging, with 63% of Ta and 61% of T1 diagnosed after the development of symptoms.…”
Section: Upper Urinary Tract Imagingmentioning
confidence: 73%
“…Sternberg et al [19] followed up 938 patients with NMIBC mainly with CT urography and demonstrated similar results. However, only 25% of patients with Ta tumors and 27% of T1 tumors who developed UTUC were diagnosed on routine imaging, with 63% of Ta and 61% of T1 diagnosed after the development of symptoms.…”
Section: Upper Urinary Tract Imagingmentioning
confidence: 73%
“…Similarly CTU may permit upper tract surveillance intervals to be increased in some patient groups and further studies are also needed. 40 Furthermore, although existing commercial and FDA approved urinary biomarkers do not have real clinical usefulness due to relatively low sensitivity and specificity, the latest generation of research platforms show significant promise in the field of urinary biomarker discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Sternberg et al retrospectively reviewed treatment and followup in 935 patients with NMIBC, of whom 51 were subsequently diagnosed with UTUCs at a median followup of 5.5 years. 40 Five and 10-year UTUC-free probability in patients with Ta tumors was 98% and 94%, respectively. During followup UTUC was diagnosed in 16 of 481 patients (3.3%) with Ta NMIBC, including 10 (2.1%) after symptoms developed and only 4 (0.8%) on routine imaging.…”
Section: Upper Tract Surveillancementioning
confidence: 94%
See 1 more Smart Citation
“…La rentabilité diagnostique des uro-scanners réalisés à titre systématique en cas d'antécédent de TVNIM reste faible (0,5 %). Toutefois, une publication récente en souligne l'intérêt en cas de signes cliniques avec une valeur prédictive positive de 63 % [12,13].…”
Section: Surveillance D'une Tumeur De La Vessieunclassified